Naming and Addressing Homophobic and Transphobic Microaggressions in Social Work Classrooms. (2nd July 2020) - Byers, David S.; McInroy, Lauren B.; Craig, Shelley L.; Slates, Sarah; Kattari, Shanna K.
ABSTRACT: Classroom-based microaggressions are a critical problem, associated with a range of negative impacts for students in targeted groups. Central to the problem of microaggressions is that they are often unacknowledged or unaddressed by educators in their own classrooms. Findings from the Social Work Speaks Out! mixed-method survey demonstrate that LGBTQ+ undergraduate and graduate students experience a range of microaggressions in social work classrooms, as they would in classes in other fields. This article draws on qualitative data to examine the experiences of homophobic and transphobic microaggressions by social work students across the United States and Canada and introduces a new tool, grounded in the data, to guide educators in recognizing, naming, and effectively addressing microaggressions in their own classrooms.